Pros and Cons of Convergence with International Financial Reporting Standards in a Developing Country: The Practitioner’s View - Abdullah, Mazni; Sapiei, Noor Sharoja (Asian Journal of Accounting Perspectives, 2013)
This study aims to gauge the practitioner’s view on convergence with International Financial Reporting Standards (IFRS) in a developing country. Semi-structured interviews with accounting practitioners were conducted to achieve this objective. While the benefits of convergence with IFRS were widely acknowledged among the respondents, they also claimed that IFRS posed a few problems and were disadvantageous to Malaysian companies. The findings from this study could give insights to the International Accounting Standards Board, standard-setters, professional accounting bodies and investors, locally and from abroad who have profiles similar to Malaysia, on how they could improve the process of convergence with IFRS.